2014
DOI: 10.1091/mbc.e13-07-0382
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic screen identifies novel mediators of collagen uptake

Abstract: Novel mediators of cell-mediated collagen turnover are identified through an RNAi screen targeting Drosophila genes with metazoan orthologues. Flotillin genes are key regulators of collagen turnover in mammalian cells and work by stabilizing expression of collagen endocytic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Furthermore, our finding that FAP ϩ fibroblasts more effectively internalize collagen compared with FAP-null cells confirms an important functional role for the protein in fibrogenesis. Our data are supported by a recent independent study where a genome-wide RNA interference screen in Drosophila S2 cells identified FAP as one of 22 candidate genes associated with increased collagen uptake (73). Finally, our data showing that FAP expression appears to modulate TGF-␤-mediated myofibroblast differentiation suggests that FAP may be very important in regulating the fibrogenic response after lung injury.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, our finding that FAP ϩ fibroblasts more effectively internalize collagen compared with FAP-null cells confirms an important functional role for the protein in fibrogenesis. Our data are supported by a recent independent study where a genome-wide RNA interference screen in Drosophila S2 cells identified FAP as one of 22 candidate genes associated with increased collagen uptake (73). Finally, our data showing that FAP expression appears to modulate TGF-␤-mediated myofibroblast differentiation suggests that FAP may be very important in regulating the fibrogenic response after lung injury.…”
Section: Discussionsupporting
confidence: 86%
“…Resuspended cells were then stained with PE-conjugated anti-CD45 and analyzed for CD45 and FITC by flow cytometry as above. In some experiments, cell surface collagen-FITC was quenched with trypan blue (200 µg/mL) prior to flow cytometry analysis as previously described(4244). …”
Section: Methodsmentioning
confidence: 99%
“…Since then, other protein cargos the UFIT pathway were identified, such as transmembrane and GPI-anchor proteins [9,[78][79][80][81][82][83][84] and extracellular proteins [85,86] (Table 3). Most of them can enter into the cell through clathrin-mediated endocytosis or other clathrin-independent pathways, such as macro-pinocytosis.…”
Section: Flotillin-mediated Endocytosis a Vesicular Trafficking Pathmentioning
confidence: 99%